Charlie Hebdo as a critical event in a secondary school: Muslim students' complex positioning in relation to the attack. (October 2021) - Tize, Carola; Berckmoes, Lidewyde; de Jong, Joop; Reis, Ria
This paper examines responses to the 2015 terror attack on Charlie Hebdo, a French satirical magazine, amongst students in a secondary school in Berlin-Neukölln, Germany. The Charlie Hebdo attack occurred in the final weeks of a 19-month ethnographic study in the community. By analyzing the responses in the school to this critical event, we identify what is at stake for Muslim students. Students presented many explanations for why the attack happened, and opinions on whether the attackers' actions were justified. Staff were alarmed about students' viewpoints that they considered "extreme". These dynamics resulted in conflicts and misunderstandings amongst students, and between students and staff. Yet, we show that, rather than the violence itself, or questions about its legitimacy, it was everyday processes in students' lives – e.g., bullying, peer pressure and discrimination, and feelings of being misrepresented and misunderstood – that were central to students' reactions to the event. We suggest that to understand students' reactions, both the immediate and the broader socio-political contexts must be considered, particularly rising xenophobia and processes of polarization in Germany and Europe at large. We thus conclude that to understand young people's reactions to terrorist acts, we need to look beyond initial statements and explore ethnographically how wider contexts shape the actions, reactions, and future orientations of young Muslims in Europe.